Sharia Insurance (Takaful) in the View of Contemporary Muamalah - Kurniawati, Reni; Assidiq, Mahfuz; Supriadi, Supriadi; Kamaruddin, Kamaruddin (YASIN, 2025)
Sharia insurance (takaful) is a Sharia-compliant financial protection system that operates on the principles of mutual assistance (ta‘āwun) and the tabarru’ (donation-based) contract, offering an ethical alternative to conventional insurance. This study was motivated by the growing interest in Sharia insurance among Indonesian Muslims seeking financial solutions aligned with Islamic law. The research aims to explore the concept of Sharia insurance from the perspective of contemporary muamalah (Islamic commercial transactions) and to analyze scholarly views regarding its legal permissibility. Utilizing a qualitative library research method, data were sourced from scientific journals, books, and relevant Islamic legal references. The findings indicate that takaful is permissible within Islamic jurisprudence when based on social contracts that avoid elements prohibited in Islamic finance, such as riba (usury), maysir (gambling), and gharar (excessive uncertainty). While some differences in scholarly opinion exist, there is broad consensus that takaful reflects a non-commercial, cooperative model consistent with Islamic ethical values. The study concludes that Sharia insurance holds strong potential as a legitimate and socially responsible protection system under Islamic law, but its broader acceptance depends on enhanced regulatory frameworks, public education, and the development of more accessible and diverse products.